Nwamatibejana- Roberto Zixaxa. The man who lived twice. - Vacha, A. (One Atlantic, many perpsectives, 2025)
Nwamatibejana, aka Zixaxa, was the powerful king of Mafumo, southern Mozambique. He led the rebellion against the colonial rule, imposing a siege to Lourenço Marques in 1894. The moment was crucial. The Portuguese crown had to react firmly since other colonial powers were looming. He was defeated in the battle of Marracuene (02/02/1895), annually commemorated in Mozambique through the Gwaza Muthini Festival. Zixaxa was the troublemaker and after the battle, received the protection of the Gaza Emperor Ngungunhane. Both ended imprisoned, firstly with their wives and then separated from them during the Azorean exile. In Angra do Heroísmo the African prisoners were formally listed as sergeants in the army, converted in the so-called civilization mission and given Christian names. Differently from the other companions (Ngungunhane, Mulungo and Godide), Zixaxa ended up embracing his new life as Roberto: he married and had kids. He turned into a well-known figure, appearing often in local newspapers. Appeals for his release came repeatedly from Brado Africano, Mozambican African press, in the 1920s. He died 20/15 years after the other prisoners, in 1927, the 31st year of exile. His heirs, in Terceira Island are still bringing both names (Roberto Zixaxa). Documentaries has been recorded in search of these “forgotten royalties”, since his memory didn’t vanish in Mozambique and Azores. In Mia Couto’s “The Drinker of Horizons” (2018), Zixaxa gains great relevance driving conclusions of the whole, internationally prized, “Sands of the Emperor” trilogy. In 2019 the Council of Angra do Heroísmo unveiled a plaque to the prisoners’ memory, in São João Batista Fortress. Later in 2022 a monument shaped as Ngungunhane, ideally directed to Mozambique, was dedicated to him and all prisoners exiled on the island. His story raises unsolved questions, but, arguably, few other political prisoners left marks on Terceira Island as he did.